Proton-driven plasma wakefield acceleration: a path to the future of high-energy particle physics - Assmann, R. (2014)
New acceleration technology is mandatory for the future elucidation of fundamental particles and their interactions. A promising approach is to exploit the properties of plasmas. Past research has focused on creating large-amplitude plasma waves by injecting an intense laser pulse or an electron bunch into the plasma. However, the maximum energy gain of electrons accelerated in a single plasma stage is limited by the energy of the driver. Proton bunches are the most promising drivers of wakefields to accelerate electrons to the TeV energy scale in a single stage. An experimental program at CERN—the AWAKE experiment—has been launched to study in detail the important physical processes and to demonstrate the power of proton-driven plasma wakefield acceleration. Here we review the physical principles and some experimental considerations for a future proton-driven plasma wakefield accelerator.